Contemporary Pandemic and Political "Ideologies": Prospects From Gandhism - Sehta, Bharti (Cultural and religious studies, 2023)
Contemporary world is not the same, after the declaration by World Health Organisation to Covid-19 as pandemic on 11th March 2020. People’s life and all aspects of it are under the grip of a myriad of questions. Where we are and where will we go? In this stage of crisis, we are experiencing a vacuum, as all available political metanarratives are unable to satisfy our needs and fail to provide opportunities of leading a good life. Political ideologies give us structures, platforms, frameworks for systematisation of thoughts upon which we create our "worldview". On the basis of these world views, economic and political systems are constructed. The present paper will inquire about how the existing world views are insufficient to create "human good" considering the case of globalization, the hyper state of which has accelerated the movement of goods, services, ideas, and people. But, this stage seems to be over by adding one more word in the list of free movements and that is "viruses". It has created a stir in the whole world and threat to human security. Similarly, the ideology of neoliberalism has focused only on "economic growth". But, it is evident now that only by developing economically, we cannot make our lives beautiful. Rather, it is lessening the rhythm and balance between human and nature day by day. The material growth has not been able to help us in contemporary pandemic so far, and there is no doubt that "matter" of this materialism alone does not matter in life. The ideology of materialism seems to get failed visualizing condition of developed world mainly America, Germany, and Italy. Communism has witnessed its downfall after the fall of USSR. Again, communist China has more or less created Covid-19 to make herself a "superpower". History has shown us how communism has locked human freedom and adversely affected transparency of any system. The biggest problem is with the ideology of utilitarianism which endorses every activity of mankind on the basis of "utility" only justifying the idea of making "greatest benefit of greatest number". This paper will inquire and critically analyse all the above mentioned ideologies and further suggest the Gandhian values, styles, and ideas for making the world a better place to live.